Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Budaya Organisasi, Sistem Pengembangan Dan Komitmen Organisasional Terhadap Kinerja HMJ Manajemen ITS Mandala - Zainal; Nely Supeni; Muhdar (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the influence of Leadership Style, Work Motivation, Organizational Culture, Development System and Organizational Commitment on the Performance of HMJ-MANAJEMEN ITS MANDALA. The data of this study were obtained from the distribution of Questionnaires to the research objects with a sampling technique using Non-Probability, namely selecting samples based on certain criteria that are relevant to the research objectives. This type of research is quantitative. The sample used in this study were members of HMJ-MANAJEMEN ITS MANDALA with a total of 100 respondents. Data analysis used Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Determination Coefficient Test (R²), t Test and F Test Using SPSS 20. The results of this study indicate that the Leadership Style variable does not have a partial effect on the Performance of HMJ-MANAJEMEN ITS MANDALA. While Work Motivation, Organizational Culture, Development System, and Organizational Commitment partially have a significant effect on the performance of HMJ-MANAJEMEN ITS MANDALA. And simultaneously the variables of Leadership Style, Work Motivation, Organizational Culture, Development System and Organizational Commitment have a significant effect on the Performance of HMJ-MANAJEMEN ITS MANDALA.